Risk Factors Influencing Seroma Formation after Modified Radical Mastectomy - Engsirora, Thawat; Chaowchuen, Sitthi (Srinagarind Medical Journal, 2021)
Background and Objectives: Many articles about seroma formation after Modified Radical Mastectomy (MRM) were published describing incidence and risk factors. No definite significant risk factors were identified as well in Udonthani Cancer hospital. The purpose of this study was to identify factors significantly associated with Seroma formation after MRM. Method: Retrospective review data of breast cancer patients who under went MRM since August 1, 2014 to October 31, 2017 were collected for identifying significant risk factors influencing seroma formation and statistically calculated by multiple logistic regression analysis. Result: During the studied period, 303 patients data were reviewed. The incidence of seroma formation was 22.77%. The only significant risk factor influencing Seroma formation was after 48 hrs. with a total drainage volume of more than 200 ml. Conclusion: The significant risk factor was after 48 hrs. with a total drainage volume of more than 200 ml. the doctor who performed the surgery and the caregiver personnel should be aware of the mentioned risk factors in order to reduce complications and for maximum security for patients.